Large scale production of lacto-N-biose I, a building block of type I human milk oligosaccharides, using sugar phosphorylases. Issue 1 (2nd January 2020) - Nishimoto, Mamoru
ABSTRACT: Human milk oligosaccharides (HMOs) have drawn attention for their contribution to the explosive bifidobacterial growth in the intestines of neonates. We found that bifidobacteria can efficiently metabolize lacto- N -biose I (LNB), the major building blocks of HMOs, and we have developed a method to synthesize LNB by applying this system. We produced LNB on a kilogram scale by the method. This proved that, among the enterobacteria, only bifidobacteria can assimilate LNB, and provided the data that supported the explosive growth of bifidobacteria in neonates. Furthermore, we were also able to reveal the structure of LNB crystal and the low stability for heating at neutral pH, which has not been clarified so far. In this paper, using bifidobacteria and LNB as examples, I describe the research on oligosaccharide synthesis that was conducted by utilizing a sugar metabolism. Abbreviations : LNB: lacto- N -biose I; GNB: galacto- N -biose; HMOs: human milk oligosaccharides; GLNBP: GNB/LNB phosphorylase; NahK: N -acetylhexosamine 1-kinase; GalT: UDP-glucose-hexose-1-phosphate uridylyltransferase; GalE: UDP-glucose 4-epimerase; SP: sucrose phosphorylase. Graphical abstract: : Lacto- N -biose I is produced from sucrose and N -acetylglucosamine with four enzymes. Catalytic amount of Inorganic phosphate and UDP-glucose are enough for this reaction.